Data Science and Applications Proceedings of ICDSA 2024, Volume 5 - Nanda, Satyasai Jagannath; Yadav, Rajendra Prasad; Gandomi, Amir H.; Saraswat, Mukesh (Lecture Notes in Networks and Systems, 2025)
XVIII, 537 p. 217 illus., 186 illus. in color.